Standardization of The Marketing Channel in Selective Distribution: The Case of Authorized Cars Sale in Poland - Janusz ZABEK (Communications of International Proceedings, 2021)
The parameters and nature of distribution channels are an important factor in product delivery. This aspect is important in the distribution of new vehicles through authorized dealerships. The main purpose of the article is to identify the standards of the selected Exclusive Representative in Poland in force in the distribution channel of new vehicles. As part of this goal, there is also the specification of individual standards, including elements such as: division, type and subject. The study found that channel standards exist at two structural levels of dealer organizations. The first level is the level of identification of the organization. Standards from this level are associated with belonging to the dealer network of a given manufacturer. The second group consists of standards at the specialist level. This level is referred to as the operational level. In other words, the second level concerns the precise conditions for delivering new cars to end customers. There is a need for more research into the standardization of product distribution channels. The acquired knowledge will allow to build more and more perfect distribution channels for products. It will be a valuable discovery in the context of introducing new products to the market.
Keywords: Marketing Channels; Standardization; Dealerships Network; Poland